Phytochemical, Biochemical and Pharmacological Properties of Plantago ovata (Ispaghula Husk) – A Review - Sutradhar, Kakoli; Tahsin, Md Rafat; Ashrafi, Sania; Ferdousy, Sonia; Akter, Tahmina; Aktar, Fahima; Chowdhury, Jakir Ahmed; Chowdhury, Abu Asad; Kabir, Shaila; Amran, Md Shah (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The plantation, evolvement, phytochemical, pharmaceutical and pharmacological properties of Plantago ovata have been reviewed to reconnoiter the plant’s diverse properties. P. ovata belonging to the family Plantaginaceae is a perennial plant native to the Mediterranean area, particularly Southern Europe, North Africa and West Asia. It has a variety of medicinal and pharmacological effects as it is frequently employed in a variety of medications for its medicinal features such as mucilage, super-disintegrant, gelling agent and suspending agent as well as pharmacological effects such as anti-diarrheal, anti-constipation, wound curer, hypocholesterolemic and hypoglycemia. That’s why, P. ovata may be utilized to make a variety of medicinal products as well as a safe and effective ethnobotanical cure for different health problems. A number of market preparations of Ispaghula are also available in the local market of Bangladesh. Information regarding diversified properties of P. ovata collected from different electronic databases (PubMed, Springer link, MDPI link, ResearchGate, Google, Google Scholar and Science Direct) have been summarized here to support the researchers to retrieve information about P. ovata. Dhaka Univ. J. Pharm. Sci. 21(2): 231-243, 2022 (December)